Identification, resistance, and susceptibility of microorganisms on healthcare workers' hands: a systematic review and meta-analysis - Juan Jairo Vaca González; Nolbedir Saza Ramírez; Fernando Rojas Páez; Julieth Yadira Serrano Riaño (Revista de Epidemiologia e Controle de Infecção)
Background and Objectives: The aim of this study is to analyze, through a systematic review and meta-analysis, the identification, resistance and susceptibility of microorganisms present in healthcare workers’ hands, identifying the most relevant antimicrobial resistant bacteria and their prevalence. Methods: Several scientific databases were reviewed to summarize contributions of the past 10 years. A meta-analysis was conducted to assess bacteria on healthcare workers’ hands and their resistance and susceptibility profiles. Results: healthcare workers were colonized by 35 types of bacteria, highlighting Staphylococcus aureus., Acinetobacter spp., and Escherichia. coli. Although a lower number of bacteria was present on healthcare workers’ hands, doctors acquired more bacteria. Specifically, health personnel contracted Enterococcus spp., Staphylococcus. epidermis, Acinetobacter spp., Escherichia. coli, among others. Resistance and susceptibility profiles showed that S. aureus was susceptible to antibiotics; nevertheless, S. aureus was resistant to ceftriaxone, erythromycin and amoxicillin-clavulanic acid. Conclusion: Detected microorganisms trigger pathologies of clinical importance such as skin infections, sepsis, gastroenteritis, among others; in addition, bacteria are the cause of pathologies of greater clinical importance, such as nosocomial pathologies due to work activity in the hospital environment, which require invasive treatment. Even if new drugs are developed, the way of prescribing and using antibiotics needs to be changed to reduce antibiotic resistance.